The Effect of Cadmium Selenide Thin Film Thickness on Carbon Monoxide Gas Sensing Properties prepared by Plasma DC-Sputtering Technique - Al-Hilli, Baha’a A.M. (Iraqi Journal of Science, 2018)
Cadmium Selenide (CdSe) thin films have been deposited on a glass substrate utilizing the plasma DC-sputtering method at room temperature at different deposition time in order to achieve different films thickness, and studied its sensitivity to the carbon monoxide CO gas which are show high response as the film thickness increases, the DC-conductivity and photoconductivity are also studied and which are increased too as the film thickness increases, that indicates the good semiconducting behavior at room temperature and light environments.